Resistance selection of triflumezopyrim in Laodelphax striatellus (fallén): Resistance risk, cross-resistance and metabolic mechanism - Wen, Shengfang; Liu, Chang; Wang, Xueting; Wang, Youwei; Liu, Chao; Wang, Jinhua; Xia, Xiaoming (Frontiers in Physiology, 2022)
Abstract The risk assessment and resistance mechanisms of insecticide resistance are critical for resistance management strategy before a new insecticide is widely used. Triflumezopyrim (TFM) is the first commercialized mesoionic insecticide, which can inhibit nicotinic acetylcholine receptor with high-performance against the small brown planthopper (SBPH), Laodelphax striatellus (Fallén). In our study, the resistance of SBPH to TFM increased 26.29-fold, and the actual heritability of resistance was 0.10 after 21 generations of continuous selection by TFM. After five generations of constant feeding under insecticide-free conditions from F16 generation, the resistance level decreased 2.04-fold, and the average resistance decline rate per generation was 0.01, but there were no statistical decline. The TFM resistant strains had no cross-resistance to imidacloprid, nitenpyram, thiamethoxam, dinotefuran, flonicamid, pymetrozine, and chlorfenapyr. The 3rd and 5th nymphal stage duration, pre-adult stage, adult preoviposition period, longevity, emergence rate, and hatchability of the resistant strain were significantly lower than those of the susceptible strain, while the female-male ratio was considerably increased. The fitness cost was 0.89. Further, cytochrome P450 monooxygenase (P450) and carboxylesterase (CarE) activities were markedly increased, but only the enzyme inhibitor piperonyl butoxide (PBO) had a significant synergistic effect on the resistant strain. The expression of CYP303A1, CYP4CE2, and CYP419A1v2 of P450 genes was significantly increased. SBPH has a certain risk of resistance to TFM with continuous application. The TFM resistance may be due to the increased activity of P450 enzyme regulated by the overexpression of P450 genes.